2011
DOI: 10.1039/c0cc05542e
|View full text |Cite
|
Sign up to set email alerts
|

An easily accessible Re-based catalyst for the selective conversion of methanol: evidence for an unprecedented active site structure through combined operando techniques

Abstract: Heterogeneous Re/SiO(2) catalysts prepared using a one pot sol-gel synthesis were found to display high activity in the direct, selective methanol conversion to methylal, which is correlated to an unprecedented rhenium oxide structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…The absence of strong peaks at high R distance is consistent with the isolated nature of the (O) 3 ReO-Si-(phenyl) 3 reference compound. With the decrease in the number of ReO bonds (3 in trioxo (O) 3 ReO-Si-(phenyl) 3 , 2 in iododioxobis (triphenylphosphine) rhenium, and 1 in trichlorooxobis (triphenylphosphine) rhenium), the intensity of the EXAFS peak at ∼1.2 Å decreases. The crystalline bulk ReO 3 reference compound contains its Re−O peak at ∼1.5 Å reflecting the longer metal−oxygen bond length in ReO 3 and absence of ReO bonds in this structure.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…The absence of strong peaks at high R distance is consistent with the isolated nature of the (O) 3 ReO-Si-(phenyl) 3 reference compound. With the decrease in the number of ReO bonds (3 in trioxo (O) 3 ReO-Si-(phenyl) 3 , 2 in iododioxobis (triphenylphosphine) rhenium, and 1 in trichlorooxobis (triphenylphosphine) rhenium), the intensity of the EXAFS peak at ∼1.2 Å decreases. The crystalline bulk ReO 3 reference compound contains its Re−O peak at ∼1.5 Å reflecting the longer metal−oxygen bond length in ReO 3 and absence of ReO bonds in this structure.…”
Section: Introductionsupporting
confidence: 83%
“…12,13 TOF-SIMS analysis of calcined supported ReO x / Al 2 O 3 catalysts also demonstrated that the surface ReO x species are essentially isolated on the alumina support. 29 The intense Re L 1 XANES pre-edge feature of the supported ReO x /Al 2 O 3 catalysts approaches that of the (O) 3 ReO-Si-(phenyl) 3 reference compound in (see Figure 2), which strongly suggests that the surface ReO x sites possess ReO 4 coordinated with only slightly different symmetry than C 3v from the reference compound. The presence of the two long Re···O bonds (2.35 Å) bonds for the deformed (110_1) surface ReO 4 structure does not appear to influence its first coordination shell and, thus, its XANES pre-edge features.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations